RAPUNZEL’S PERSONALITY ANALYSIS IN “TANGLED” MOVIE WITH PSYCHOANALYSIS - damin, Faradina Izza Hamida; Nurul Fadhillah; Muhammad Ilham, (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
Psychoanalysis can be interpreted as a theory that explains personality changes in a person. The purpose of this research is to analyze the main character’s personality and factors in the Tangled movie. This research uses descriptive qualitative and started by explaining the id, ego, and super-ego theory by Sigmund Freud (1954). The results of the analysis showed that there are 23 pieces of data in this research that include three structural personalities such as id, ego, and super-ego. The researcher found some factors that impact Rapunzel’s personality which are heredity (8), family environment (9), cultural environment (2), and social environment (4) that appears in “Tangled” movie.